Agricultural Land Utilization Its Problems, Planning and Prospects in Khagaria District: A Geographical Study: Exploring Agricultural Land Utilization and Planning in Khagaria District (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Use of geographical area under different purpose is commonly known as land use the agriculture is the most dominant feature of the district. The proper management and sustainable use of land can has to improve the ecosystem and its productivity of a particular region and it may also manage of a particular region and it may also manage a balance between human being and natural a balance between human being and natural resources. The total reported area of district Khagaria was 148572.36 hectares out of which a big proportion of 94729.74 hectares (63.76 percent) orchards and Groves 936.01 hectares (0.63 percent) uncultivable land 6715.47 hectares (4.52percent) culturable wastе land 19626.41 hectares (13.21percent) Area not available for cultivation 8929.20 hectares (6.01 percent) pasture and grazing land 3149.73 hectares (2.12 percent) and forest 5660.61 hectares (3.81 percent) in 2011-12. A Comprehensive planning for the development in the agriculture of Khagaria district has given after careful preparation of local land use survey.